لکھنوی غزل میں نعتیہ عناصر: Nʻatiya Elements in Lucknwī Ghazal (Al-Qamar, 2023)
Naat is a sacred Genre of Literature that is the interpretation and explanation of Dignities of the Holy Prophet Hazrat Muhammad (SAWW). Naat writing is the written expression of the Love of the Holy Prophet. In it the poet expresses his slavery of the Holy Prophet in various ways. The word Naat does not indicates the Genre but the theme and topic. Naat may be written in Qaseeda, Masnvi, Ghazal, Rubaee, Qataa, Muustzad, Tarjee band, Masnvi, Musallas, Nazam and any other form. The poets of Lucknow school of thought have expressed their love for the Holy Prophet in various forms of poetry. In this article I shall point out the Ghazal form of poetry in the Naats of Lucknow school of thought. Ghazal is the most popular form of Urdu poetry. Its meaning of dictionary is the conversations with women, expression of love and beauty. In the beginning this genre of poetry was limited to internal expression. Gradually it got the vastness of expression and in accumulated the topics and themes of the whole world. Every verse of it is one complete unit form meaningful point of view.
Keywords: Prophet; Sword; Asset; Prophet’s biography; Universe; Amalgam; Passion